2018
DOI: 10.1038/s41467-018-03138-7
|View full text |Cite
|
Sign up to set email alerts
|

Operando spectroscopy study of the carbon dioxide electro-reduction by iron species on nitrogen-doped carbon

Abstract: The carbon–carbon coupling via electrochemical reduction of carbon dioxide represents the biggest challenge for using this route as platform for chemicals synthesis. Here we show that nanostructured iron (III) oxyhydroxide on nitrogen-doped carbon enables high Faraday efficiency (97.4%) and selectivity to acetic acid (61%) at very-low potential (−0.5 V vs silver/silver chloride). Using a combination of electron microscopy, operando X-ray spectroscopy techniques and density functional theory simulations, we cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(220 citation statements)
references
References 49 publications
14
205
0
1
Order By: Relevance
“…With the development of advanced instruments and characterization techniques, researchers are able to gain deeper insight into the structure of single atoms in the SACs, including its chemical environment and spatial structure. In this section, we would review the specific technologies for analyzing the structure of SACs.…”
Section: Fabrication Of Densely Populated Sacsmentioning
confidence: 99%
“…With the development of advanced instruments and characterization techniques, researchers are able to gain deeper insight into the structure of single atoms in the SACs, including its chemical environment and spatial structure. In this section, we would review the specific technologies for analyzing the structure of SACs.…”
Section: Fabrication Of Densely Populated Sacsmentioning
confidence: 99%
“…Moreover, a systematic investigation by Huan et al into Fe SACs revealed that by tuning ratio of isolated Fe–N 4 sites compared to Fe nanoparticles, the CO:H 2 ratio can be tuned . The importance of Fe‐N coordination was further revealed by Genovese et al who utilized operando XAS and DFT to confirm the role of nitrogen‐coordinated Fe (II) single atom sites as responsible for the conversion of CO 2 to acetic acid at extremely low applied potential of −0.5 V versus Ag/AgCl . Overall, Fe SACs can be shown to demonstrate CO 2 RR activity that is greater than that of Co SACs .…”
Section: Active Sites In Metal‐carbon Catalystsmentioning
confidence: 99%
“…Charge and spin can be carefully tuned in surface-confined metal-organic networks, at least in UHV, and we tackle here the issue whether this fundamental bottom-up approach can be extended beyond the surface science UHV environmental constraints. Recently, the reactivity of tetrapyrrole monolayers at surfaces has been investigated in situ at the solid/liquid interface under electrochemical conditions, mainly by STM methods [20,[132][133][134][135][136][137][138][139][140][141][142]. Very recently, instead, surface science spectroscopic approaches combining SFG and NAP-XPS methods allowed extension of the investigations of the ligand-macrocycle interaction up to the mbar pressure regime at room temperature, thus close to applicative relevant conditions [14,37,99,105,108].…”
Section: A Fundamental Approach Beyond Uhvmentioning
confidence: 99%